Incidence of mature adipocytic component within cutaneous smooth muscle neoplasms. (11th August 2016) - Jones, Chelsea; Shalin, Sara C.; Gardner, Jerad M.
Abstract : Angioleiomyoma is a benign smooth muscle tumor of the subcutis. The presence of mature adipocytes has been described in this tumor under the rubric of 'angiolipoleiomyoma' or, erroneously, 'angiomyolipoma' (these are not PEComas). Previous studies have found adipocytes in only 2–3% of angioleiomyoma. Anecdotally, the incidence appeared to be greater than this in our practice. Moreover, the presence of adipocytes has not been evaluated in pilar leiomyoma or cutaneous leiomyosarcoma. We searched the pathology archives from 2007 to 2014 for all cutaneous and subcutaneous leiomyoma and leiomyosarcoma; cases were reviewed to confirm the diagnosis and evaluate for mature adipocytes. Seven of 73 total cases (10%) contained mature adipocytes: 1 of 33 pilar leiomyoma (3%), 4 of 22 angioleiomyoma (18%) and 2 of 18 leiomyosarcoma (11%). In our series, the 18% incidence of 'angioleiomyoma with fat' (our preferred terminology) is higher than the previously reported incidence of 2–3%. We also report the rare presence of mature adipocytes within pilar leiomyoma and cutaneous leiomyosarcoma, a finding not previously reported to our knowledge. Mature adipocytes may be present within cutaneous and subcutaneous leiomyomas and leiomyosarcomas and should not detract from the diagnosis or lead to concern for an adipocytic neoplasm or PEComa.